Ljubezen na papirju - vloga notarja pri urejanju premoženjskih razmerij zakoncev - Erjavec, Nataša (Podjetje in delo, 2018)
A reform of family law brings about important novelties and changes in the field of marital property agreements, either during the course of marriage, in the event of a divorce or death of a spouse. As deeds of gift are frequent among legal transactions concluded between spouses during a marriage, the article discussed them in detail, particularly ordinary small gifts. An important novelty is the possibility of a conclusion of marital property agreements, by which spouses may exclude and change the legal property regime. Just like any other legal transaction between spouses, a marital property agreement is concluded in the form of a notarial deed. The role of a notary in the field of a family law is growing. Before concluding a marital property agreement, a notary shall give spouses impartial advice and make sure that they both fully understand the meaning and legal consequences of a marital property agreement they wish to conclude; the notary shall likewise make sure that the content of the agreement is not in contravention of the Constitution, mandatory regulations and moral principles. A new register of marital property agreements is being introduced, maintained by the Chamber of Notaries of Slovenia. As regards divorce, there is yet another important novelty - the possibility of a consensual divorce before a notary. This private divorce without involvement of a court enables spouses without joint underage children to conclude an agreement on the division of co-owned property, which of them remains or becomes a tenant after the divorce, and maintenance of the dependent spouse. All these could have consequences in the event of a death of one of the spouses. Albeit on a very limited scale, this new regime will have an impact on the field of planning the succession of spouses.
Keywords: darilna pogodba; notar; pogodba o ureditvi premoženjskih razmerij; razveza zakonske zveze; smrt zakonca; sporazumna razveza pred notarjem; zakonca